Smart education in remote areas: collaborative strategies to address challenges in Majene Regency, Indonesia - Sapiah, Sitti; Ulfah, St. Maria; Saputra, Aco Nata; Hardi, Rudi (Frontiers in Education, 2025)
IntroductionThis study investigates the critical factors influencing the successful implementation of Smart Education in Majene Regency, with particular attention to trust, communication, commitment, educational foundations, educational pillars, and educational benefits. The initiative responds to the growing need for digital transformation in education, particularly in remote areas.MethodsA quantitative research design was employed, involving 345 respondents selected through purposive sampling from institutions that actively implement Smart Education. Data were collected using a structured questionnaire consisting of 57 items measured on a 5-point Likert scale. The data were analysed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), a technique suitable for moderate sample sizes, complex models, and non-normal data distributions.ResultsThe analysis identified trust as the most dominant factor influencing Smart Education adoption, surpassing communication, commitment, and service quality. A strong educational foundation and the tangible benefits of education—such as upskilling and employment opportunities—significantly enhanced stakeholder perceptions and service quality. In contrast, the educational pillar and communication variables showed limited direct effects but functioned as catalysts when combined with trust and educational foundations.DiscussionThe findings highlight the central role of trust and stakeholder engagement in supporting the digital transformation of education in peripheral regions. While commitment plays a supportive role, its limited influence underscores the importance of long-term sustainability and institutional dedication. The minimal impact of communication and service quality as standalone factors suggests that their effectiveness is maximised when embedded within a broader trust-based strategy. Moreover, aligning educational benefits with local labour market demands reinforces the strategic relevance of Smart Education initiatives. Overall, the study underscores that the harmonisation of trust, commitment, and strong educational foundations is crucial for sustaining Smart Education transformations in geographically remote areas.